Analisis Respon Kredit Dan Pembiayaan Industri Perbankan Di Indonesia - Mulia Amirullah; Abrista Devi (MALIA: Journal of Islamic Banking and Finance, 2020)
This study aims to measure the productive credit performance of conventional banks and profit-sharing financing for Islamic banks and analyze their responses to the shock of macroeconomic variables. In this study, the analysis method used is the Vector Auto-Regressive (VAR) / Vector Error Correction Model (VECM). The data observed in this study are monthly data from the period 2015 to 2019. The results showed that NPL (Non Performing Loan) was responding negatively to the shock of the productive credit, meanwhile NPF (Non Performing Financing) was responding positively to the shock of the profit-sharing financing. NPL have the most dominant contribution to the productive credit of conventional bank. Meanwhile, world oil prices are projected as the highest contribution to the profit-sharing financing for Islamic banks. Conventional bank productive credit affects inflation. The world crude oil price (OIP) affects the problematic financing of Islamic banks. The price of crude oil affects the exchange rate, and the exchange rate affects inflation.